2013
DOI: 10.1002/jez.1847
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naloxone, serotonin, and dopamine on reproduction of the freshwater crabBarytelphusa guerini

Abstract: Several investigators suggest a relationship between neurotransmitters, serotonin (also called 5-hydroxytryptamine, 5-HT), and dopamine (DA) in the regulation of growth and reproductive development of vertebrate species, rather than the invertebrate species. In this study, we evaluated the role of 5-HT and DA in reproductive development of an invertebrate species, the freshwater crab Barytelphusa guerini. We tested the effects of 5-HT both alone and combined, and also the effects of an opioid antagonist naloxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…In agreement with the present observations, dopamine injection in P. clarkii displayed low testicular index and acinar diameter values, fewer mature spermatozoa and poorly developed androgenic glands (Sarojini et al, 1994;. In U. pugilator and B. guerini, Sarojini et al (1993) and Prasad et al (2014) documented low values for testicular index and acinar diameter following dopamine treatment. Poljaroen et al (2011) and Siangcham et al (2013) reported significantly low testicular index, acinar diameter and germ cell proliferation and more number of immature spermatocytes in M. rosenbergii administered with dopamine.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with the present observations, dopamine injection in P. clarkii displayed low testicular index and acinar diameter values, fewer mature spermatozoa and poorly developed androgenic glands (Sarojini et al, 1994;. In U. pugilator and B. guerini, Sarojini et al (1993) and Prasad et al (2014) documented low values for testicular index and acinar diameter following dopamine treatment. Poljaroen et al (2011) and Siangcham et al (2013) reported significantly low testicular index, acinar diameter and germ cell proliferation and more number of immature spermatocytes in M. rosenbergii administered with dopamine.…”
Section: Discussionsupporting
confidence: 92%
“…A similar elevation in testicular index, acinar diameter, proportion of mature spermatozoa and active proliferation of spematogonial cells was observed in M. rosenbergii following serotonin administration (Poljaroen et al, 2011;Siangcham et al, 2013). Prasad et al (2014) observed a significant boost in testicular index and mean acinar diameter in a dose dependent manner in serotonin injected B. guerini. Treatment with leucine enkephalin, a stimulatory neurotransmitter, drastically enhanced the testicular index and mean acinar diameter values in the freshwater field crab Oziotelphusa senex senex (Reddy, 2003) and the eastern lubber grasshopper Romalea microptera (Kumar et al, 2013).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It may provide a cheap alternative to chemical grade serotonin. The opioid antagonist, naloxone hydrochloride dihydrate, was found to reliably induce reproductive development in the freshwater crab species, Barytelphusa guerini ( Prasad et al, 2014 ). Both these latter chemicals are believed to work by either up-regulating gonad stimulating hormone (GSH) or down-regulating gonad inhibiting hormone (GIH) ( Niaraki, Subramanian & Moghissi, 1982 ; Prasad et al, 2014 ; Van Bergeijk et al, 1986 ).…”
Section: Introductionmentioning
confidence: 99%
“…The opioid antagonist, naloxone hydrochloride dihydrate, was found to reliably induce reproductive development in the freshwater crab species, Barytelphusa guerini ( Prasad et al, 2014 ). Both these latter chemicals are believed to work by either up-regulating gonad stimulating hormone (GSH) or down-regulating gonad inhibiting hormone (GIH) ( Niaraki, Subramanian & Moghissi, 1982 ; Prasad et al, 2014 ; Van Bergeijk et al, 1986 ). Phosphate is a primary ingredient in many lawn fertilizer products and has been identified as a pollutant of many coastal environments, including the Florida Keys, through waste-water and storm-water runoff from lawns ( Corbett et al, 2000 ; Dillon et al, 2003 ; Lapointe, O’Connell & Garrett, 1990 ).…”
Section: Introductionmentioning
confidence: 99%